THE RELATIONSHIP OF EXCLUSIVE BREASTFEEDING WITH THE INCIDENT OF DIARRHEA IN BABIES AGED 0-6 MONTHS - Endang Sihaloho; Selvia Yolanda Dalimunthe; Mery Krista Simamora; Ristiani Ristiani (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Exclusive breastfeeding is essential to protect babies/children from the risk of infectious diseases. Diarrhea, which is the contagious disease that causes mortality and morbidity in second place in children under five years of age (toddlers), is thought to be related to the low level of exclusive breastfeeding. This research aims to determine the relationship between exclusive breastfeeding and the incidence of diarrhoea in babies aged > 0-6 months. This type of research is observational analytic using a cross-sectional design and a retrospective approach. The research population came from babies at the Pasar Merah Community Health Center in 2023. The research sample was 66 babies. Analysis of the relationship between variables was carried out using the chi-square test. The research results were obtained from 66 respondents; 6 (20.7%) babies were exclusively breastfed and suffered from diarrhoea, and 23 (34.8%) did not. Meanwhile, 29 (43.9%) babies who were not solely breastfed suffered from diarrhoea, and only 8 (12.1%) did not suffer from diarrhoea. The results of the chi-square test obtained a p-value = 0.000. The research conclusion shows that exclusive breastfeeding is related to the incidence of diarrhoea in babies aged 0-6 months.